2014
DOI: 10.1089/rej.2013.1512
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans in Chinese Medicinal Studies: Making the Case for Aging and Neurodegeneration

Abstract: Aging is a progressive process with degenerative changes of various tissues and organs. As a classic model organism in genetics and neurobiology, Caenorhabditis elegans is also a powerful system in aging and behavioral studies and can be used at both the molecular and organismal levels to evaluate potential therapeutics for age-related neurodegeneration, owing to its short life span, relative simplicity, and high degree of experimental tractability as well as significant conservation of disease genes and signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…As lifespan is regarded as an unequivocal anti-aging index [ 22 ], we further investigated the effect of AsiPeps on the lifespan of C. elegans and showed that the lifespan of the nematodes was indeed extended after treatment with 2.0 and 4.0 mg/mL of the peptides ( Figure 5(b) ). Since the nematodes may cut down their consumption of food if a test sample is distasteful, dietary restriction, which is well known to retard development and delay aging in C. elegans [ 41 ], may contribute to the lifespan-extending effect of AsiPeps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As lifespan is regarded as an unequivocal anti-aging index [ 22 ], we further investigated the effect of AsiPeps on the lifespan of C. elegans and showed that the lifespan of the nematodes was indeed extended after treatment with 2.0 and 4.0 mg/mL of the peptides ( Figure 5(b) ). Since the nematodes may cut down their consumption of food if a test sample is distasteful, dietary restriction, which is well known to retard development and delay aging in C. elegans [ 41 ], may contribute to the lifespan-extending effect of AsiPeps.…”
Section: Resultsmentioning
confidence: 99%
“…The lifespan assay was performed in 96-well plates using liquid culture as previously described [ 21 ]. The number of live nematodes was scored microscopically every 2 days based on their mobility, shape, and pharyngeal pumping until all the nematodes died [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although C. elegans is a tiny organism (~1 mm in length), it contains about two-thirds of the potential counterparts of human disease genes and nearly one-third of its somatic cells are neurons [13]. Along with its short lifespan, genetic tractability and multiple behavioral phenotypes, this nematode model also offers special advantages in studies of age-onset neurodegenerative disorders [14]. For example, the pan-neuronal expression of human Aβ42 protein in C. elegans strain CL2355 causes behavioral deficits in chemotaxis, associative learning and thrashing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, sequence information and regulation mechanisms of bioactive peptides in M. meretrix are lacking. Here we first examined the in vivo antioxidant properties of a peptide-rich extract of M. meretrix using Caenorhabditis elegans , a powerful model animal widely used in biomedical studies [ 26 ]. After separation of the antioxidant peptide fractions, we then identified the peptide sequences and synthesized the peptides for bioactivity studies.…”
Section: Introductionmentioning
confidence: 99%